Risk of Diabetic Ketoacidosis and Hyperglycemic Hyperosmolar State Associated with the Use of Antipsychotic Drugs - Haddad, Nisrine (Université d'Ottawa / University of Ottawa, 2023)
Antipsychotic drugs (APDs) are classified into two classes: typical or first-generation antipsychotics (FGAs), and atypical or second-generation antipsychotics (SGAs). The mechanisms of actions by which these two classes mediate their effects overlap, but with some notable differences. Atypical antipsychotics have been associated with the metabolic syndrome (MetS) defined as increase weight, increased diabetes and glucose abnormalities, and dyslipidemia. In recent years, accrued evidence has shown that atypical APDs are associated with adverse diabetic complications, namely diabetic ketoacidosis (DKA) and hyperglycemic hyperosmolar state (HHS). APDs, both typical and atypical, are critical for the treatment mental disorders such as schizophrenia and bipolar disorder. In addition, they are used off-label to treat other neurological and behavioural conditions such as obsessive-compulsive disorders, Tourette’s syndrome, anxiety, and agitation. Therefore, it is crucial to have a better understanding the association between DKA or HHS and these important medicines. This thesis comprises five studies that examine the relationship between adverse events of DKA or HHS and treatment with APDs that were approved for use by the United States Food and Drugs Administration (US FDA). Chapters 2 and 3 are two systematic reviews that summarize findings from 125 case reports and 13 observational studies, respectively. Findings summarized in Chapter 2 support an association between atypical APD use and DKA or HHS. Chapter 3 summarizes findings from five analytical and eight descriptive observational studies, which suggest a possible association between atypical APDs and DKA. Chapter 4 explores safety signals associated with atypical APDs and adverse DKA events using the US FDA Adverse Events Reporting System (FAERS). Results from this analysis corroborate the conclusions drawn from Chapters 2 and 3. Chapters 5 and 6 present analyses of electronic health records (EHRs), comprising real-world data in the Cerner Health Facts® (Health Facts) database collected between 2000 and 2016. An analysis of the temporal patterns of APD use is presented in Chapter 5, both atypical and typical APDs as a class and for individual drugs. While atypical APD use increased in the US overtime, an overall decrease was observed for typical antipsychotics. The results of a nested-case control study examining the association between DKA and APDs by class and by individual drugs are presented in Chapter 6. Findings do not support an association between antipsychotic drugs and DKA. However, subgroup analyses by age group and level of comorbidity provide additional evidence of potential associations for certain higher risk populations, particularly the elderly and those suffering with multiple comorbidities. The findings presented in the five chapters support a possible association between DKA adverse events and atypical APD use. While there is insufficient evidence to present conclusions for HHS, future research is warranted to better understand the association between these drugs and diabetic complications.
Keywords: Antipsychotic Drugs; Diabetic Ketoacidosis; Hyperglycemic Hyperosmolar State; Electronic Health Records; FDA Adverse Events Reporting System; Diabetic Complications; Nested Case Control